2021
DOI: 10.1177/19427786211024264
|View full text |Cite
|
Sign up to set email alerts
|

Taking togetherness apart: From digital footprints to geno-digital spores

Abstract: Increasingly, the lines of our lives are prescribed, mediated, drawn and knotted together by digital technologies. It has been argued that ‘digital footprints’, as a trail of user data points collected from online communities and networks, can assist in better understanding human behaviour and social interaction, initially focused on mainly real-time and retrospective analysis. In our attempts at sense-making of togetherness in a COVID-19/post-COVID-19 world, we believe it may be an oversimplification to conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Studies have shown that age, sex, health status, and concomitant diseases and other self-factors have been identified as potential risk factors affecting the prognosis of patients. [2] Seventy-five percent of elderly patients were suffering from cardiovascular diseases, respiratory illnesses, cognitive impairments, and osteoporosis before they had surgery, [3] which remarkably augmented postoperative complications and mortality. [4] Because patients need absolute bed rest after fracture, it not only reduces the life quality but also makes them prone to complications of cerebral infarction and deep vein thrombosis in the lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that age, sex, health status, and concomitant diseases and other self-factors have been identified as potential risk factors affecting the prognosis of patients. [2] Seventy-five percent of elderly patients were suffering from cardiovascular diseases, respiratory illnesses, cognitive impairments, and osteoporosis before they had surgery, [3] which remarkably augmented postoperative complications and mortality. [4] Because patients need absolute bed rest after fracture, it not only reduces the life quality but also makes them prone to complications of cerebral infarction and deep vein thrombosis in the lower limbs.…”
Section: Introductionmentioning
confidence: 99%